2014
DOI: 10.1002/jbm.a.35268
|View full text |Cite
|
Sign up to set email alerts
|

Improving the mechanical properties of collagen‐based membranes using silk fibroin for corneal tissue engineering

Abstract: Although collagen with outstanding biocompatibility has promising application in corneal tissue engineering, the mechanical properties of collagen-based scaffolds, especially suture retention strength, must be further improved to satisfy the requirements of clinical applications. This article describes a toughness reinforced collagen-based membrane using silk fibroin. The collagen-silk fibroin membranes based on collagen [silk fibroin (w/w) ratios of 100:5, 100:10, and 100:20] were prepared by using silk fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 33 publications
2
65
1
Order By: Relevance
“…Suture experiments were conducted in vitro by hanging a 5 g weight, as previously described. 15 The 5 g weight was used to simulate the force of the suture. Before the surgery, the membrane was soaked in deionized water for more than 1 h until saturation.…”
Section: Evaluations Of the Mechanical Properties And Suture Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Suture experiments were conducted in vitro by hanging a 5 g weight, as previously described. 15 The 5 g weight was used to simulate the force of the suture. Before the surgery, the membrane was soaked in deionized water for more than 1 h until saturation.…”
Section: Evaluations Of the Mechanical Properties And Suture Experimentsmentioning
confidence: 99%
“…Studies have reported the use of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) and N-hydroxysuccinimide (NHS) to crosslink collagen. 11,[13][14][15] EDC is a carboxyl and amine reactive zero length crosslinker, which reacts initially with the carboxyl group and forms an O-acylisourea intermediate. This intermediate reacts quickly with an amino group to form an amide bond and then releases an isourea byproduct.…”
Section: Introductionmentioning
confidence: 99%
“…An engineered corneal replacement has to withstand suturing during surgery (74) This article has been peer-reviewed and accepted for publication, but has yet to undergo copyediting and proof correction. The final published version may differ from this proof.…”
mentioning
confidence: 99%
“…An alternative use of silk fibroin has been as a reinforcing element in collagen-based membranes. [35] This has potential to take advantage of the increased cell interaction with the collagen component and the increased mechanical properties of the fibroin component.…”
Section: Other Natural Polymers: Silks and Keratinmentioning
confidence: 99%